Bioactive Hybrid Material with Applications in Dental Medicine - Totu, Eugenia Eftimie; Isildak, Selim; Petre, Daniel Costinel; Isildak, Ibrahim; Cristache, Corina Marilena; Tavukcuoglu, Ozlem; Buga, Roxana Madalina; Yildirim, Ridvan; Totu, Tiberiu (IEEE, 2019)
The present work proposes a hybrid material based on a porous titanium skeleton with an accommodated complex pharmaceutical mixture of melatonin, hyaluronic acid, and antibiotics that could be applied for soft tissues' regeneration. Direct usage of the newly developed hybrid bioactive system is dental medicine for periodontal wound treatment. The experimental results highlight the preservation of the specific characteristic of each component of the proposed formulation. The synergy of the bioactive compounds used in our complex hybrid material provides an antimicrobial and anti-inflammatory action combined with the immunomodulatory effect for improved topical therapy in moderate periodontitis.
Keywords: hybrid material; melatonin; hyaluronic acid; antibiotic; periodontitis; TOPICAL TREATMENT; HYALURONIC-ACID; THERAPY; Health Care Sciences & Services; Engineering; Medical Informatics